The rivers of paradise : Moses, Buddha, Confucius, Jesus, and Muhammad as religious founders - Freedman, David Noel, 1922-2008.; McClymond, Michael J., 1958- (Grand Rapids, Mich. : W.B. Eerdmans, 2001)
This important volume explores the lives of the five founders of major world religions--Moses, Buddha, Confucius, Jesus, and Muhammad--chronicling what is actually known of these charismatic men and introducing readers to the cultural and religious worlds that heard their messages. Readers in predominantly Christian lands, in addition to learning about the lives of Confucius, Buddha, and Muhammad--whom they might not be familiar with--will also be introduced to modern research now casting fresh light on the careers of Moses and Jesus. Whether studied individually or in comparison with one another, these biographies, together with a chapter on the characteristics of religious leadership, chart the spiritual rivers that continue to feed the diversity of religious expression today.
Moses, Torah, and Judaism / Carl S. Ehrlich -- Shakyamuni : Buddhism's founder in ten acts / Richard S. Cohen -- Confucius / Mark Csikszentmihalyi -- Jesus / Michael J. McClymond -- Muhammad / Daniel C. Peterson -- Prophet or loss? : reassessing Max Weber's theory of religious leadership / Michael J. McClymond -- Final thoughts : responses to McClymond's "Prophet or loss?"
Includes bibliographical references and index.
Keywords: Religious biography; Religions